Suzanne Newcombe. 2019. Yoga in Britain. Stretching Spirituality and Educating Yogis. Bristol: Equinox. 324 pp. ISBN 9781781796597 - Muñoz García, Adrián (Estudios de Asia y África, 2021)
Suzanne Newcombe. 2019. Yoga in Britain. Stretching Spirituality and Educating Yogis. Bristol: Equinox. 324 pp. ISBN 9781781796597